Prelom s staro miselnostjo, da je gost zadovoljen, če dobi kranjsko klobaso in liter vina - Mlekuž, Jernej (Etnolog. Nova vrsta (Ljubljana), 2014)
Since its first mention in the Slovene papers in 1849, the Carniolan sausage has shown the kind of symbolic stability, continuity, and endurance that would be hard to find with other material objects identified with Slovenehood or national symbols. But even the Carniolan sausage has not always enjoyed unproblematic continuity of the same content - one that would have been preserved in the same form through time. In particular not when a time comes along that more or less turns everything upside down - a time of revolution. The article explores what happened to the Carniolan sausage in the socialist period that was marked by revolution, i.e. a period when many things which reminded people of previous times were considered unwanted. In spite of the new regime's often negative attitude towards the Carniolan sausage, it partly managed to preserve its symbolic, signifying potential. It continued to be identified, as in the times before the revolution, with Slovenehood and things "smeared" with Slovenehood. But it also started to be identified with past time or "traditions", which the "new times" often preferred to forget about or simply erase, though at times they also indulged in nostalgically sweet memories. The Carniolan sausage has several identification elements, resulting in syncretism and consequently in changes, promotion, and intermixture. The Carniolan sausage thus has not become an outdated identification element, but living, continuous communication, which belongs to several generations, participates in a variety of traditions, and has inherited several legacies. As indicated by the period of the first Yugoslavia, this does not necessarily mean that the result is harmonious or conflictless.
Keywords: ethnology; etnologija; narodni simboli; national symbols; kranjska klobasa; Carniolan sausage; socialism; socializem; Slovenian newspapers; slovensko časopisje; zgodovinski pregledi